The role of social media in clinical excellence. (July 2014) - Batt‐Rawden, Samantha; Flickinger, Tabor; Weiner, John; Cheston, Christine; Chisolm, Margaret
Summary Background The provision of excellent patient care is a goal shared by all doctors. The role of social media (SM) in helping medical students and doctors achieve clinical excellence is unknown. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Social media may help facilitate the achievement of clinical excellence </boxed-text> Purpose This report aimed to identify examples of how SM may be used to help promote the achievement of clinical excellence in medical learners. Methods Three of the authors previously conducted a systematic review of the published literature on SM use in undergraduate, graduate and continuing medical education. Two authors re‐examined the 14 evaluative studies to identify any examples of SM use that may facilitate the achievement of clinical excellence and to consider whether there were any aspects of clinical excellence for which no studies had been performed, and, if so, whether SM was relevant to these domains. Results Each study touched on one or more of the following domains of clinical excellence: communication and interpersonal skills; professionalism and humanism; knowledge; diagnostic acumen; exhibiting a passion for patient care; a scholarly approach to clinical practice; and explicitly modelling expertise to medical trainees. No study addressed the role of SM to promote the skillful negotiation of the health care system, and in collaboration with investigators to advance science and discovery; however, additional evidence suggested that SM may play an adjunctive role in promoting the achievement of these aspects of clinical excellence. Conclusion This report supports the hypothesis that SM may help facilitate the achievement of clinical excellence; however, further research is needed into the role of SM in promoting the achievement of clinical excellence.